Literature Review : Peran Konseling Kelompok dalam Menemukan Solusi Personal yang Efektif - Rizky Al Akbar Irawan; Tabitha Zahra; Bunga Aulia; M. Aziz Andreansyah; Ratna Sari Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Every student must have personal problems both from behavior to emotional, especially in the context of education, so that these problems can interfere with the process of self-development. This can be overcome with the help of group counseling. The purpose of this study is to determine the effectiveness of group counseling in finding solutions to students’ personal problems. The method used is the literature study method, which obtains research from various reading sources such as journals. This research produces evidence from various literatures that group counseling is very effective in finding solutions to students’ personal problems both from behavior to emotional problems. Therefore, group counseling services are highly recommended for guidance and counseling in schools to be carried out regularly and periodically to help students overcome their problems effectively.